Silicon photonics interfaced with microelectronics for integrated photonic quantum technologies: a new era in advanced quantum computers and quantum communications?. Issue 10 (13th February 2023) - Gupta, Rajeev; Singh, Rajesh; Gehlot, Anita; Akram, Shaik Vaseem; Yadav, Neha; Brajpuriya, Ranjeet; Yadav, Ashish; Wu, Yongling; Zheng, Hongyu; Biswas, Abhijit; Suhir, Ephraim; Yadav, Vikram Singh; et al.
Abstract : Silicon photonics is rapidly evolving as an advanced chip framework for implementing quantum technologies. Abstract : Silicon photonics is rapidly evolving as an advanced chip framework for implementing quantum technologies. With the help of silicon photonics, general-purpose programmable networks with hundreds of discrete components have been developed. These networks can compute quantum states generated on-chip as well as more extraordinary functions like quantum transmission and random number generation. In particular, the interfacing of silicon photonics with complementary metal oxide semiconductor (CMOS) microelectronics enables us to build miniaturized quantum devices for next-generation sensing, communication, and generating randomness for assembling quantum computers. In this review, we assess the significance of silicon photonics and its interfacing with microelectronics for achieving the technology milestones in the next generation of quantum computers and quantum communication. To this end, especially, we have provided an overview of the mechanism of a homodyne detector and the latest state-of-the-art of measuring squeezed light along with its integration on a photonic chip. Finally, we present an outlook on future studies that are considered beneficial for the wide implementation of silicon photonics for distinct data-driven applications with maximum throughput.